Host-Microbial Interactions in Systemic Lupus Erythematosus and Periodontitis - Pessoa, Larissa; Aleti, Gajender; Choudhury, Saibyasachi; Nguyen, Daniel; Yaskell, Tina; Zhang, Yun; Li, Weizhong; Nelson, Karen E.; Neto, Leopoldo Luiz Santos; Sant'Ana, Adriana C. P.; Freire, Marcelo (Frontiers in Immunology, 2019)
Background: Systemic lupus erythematosus (SLE) is a potentially fatal complex autoimmune disease, that is characterized by widespread inflammation manifesting tissue damage and comorbidities across the human body including heart, blood vessels, joints, skin, liver, kidneys, and periodontal tissues. The etiology of SLE is partially attributed to a deregulated inflammatory response to microbial dysbiosis and environmental changes. In the mouth, periodontal environment provides an optimal niche for local and systemic inflammation. Our aim was to evaluate the reciprocal impact of periodontal subgingival microbiome on SLE systemic inflammation. Methods: Ninety-one female subjects were recruited, including healthy (n=31), SLE-inactive (n=29), and SLE-active (n=31). Patients were screened for probing depth, bleeding on probing, clinical attachment level, and classified according to CDC/AAP criteria with or without periodontal dysbiosis., periodontitis. Serum inflammatory cytokines were measured by human cytokine panel and a targeted pathogenic subgingival biofilm panel was examined by DNA-DNA checkerboard from from gingival crevicular fluid (GCF) of the same subjects. sungingival plaque samples. Results: The results showed significant upregulation of serum proinflammatory cytokines in individuals with SLE when compared to controls. Stratification of subject’s into SLE-inactive (I) and SLE-active (A) phenotypes or periodontitis and non-periodontitis groups provided new insights into SLE pathophysiology. Eleven Ten proinflammatory cytokines were upregulated in GCF serum of SLE-I only and one in SLE-A only. Four molecules overlapped in SLE-A and SLE-I. Anti-A potent anti-inflammatory cytokines included IL-4, IL-10, was which were upregulated in SLE-I sera (but not SLE-A), controlling clinical phenotypes. Out of twenty-four significant differential oral microbial abundances found from GCF in SLE, fourteen unique subgingival bacteria profiles were found to be elevated in SLE. The most severe oral pathogens (Treponema denticola and Tannerella forsythia) showed increase abundances on SLE-A periodontal sites when compared to SLE-I and healthy controls. Inflammation, as measured by cytokine-microbial correlations, showed that periodontal pathogens dominating the environment increased proinflammatory cytokines systemically. Conclusions: Altogether, low-grade systemic inflammation that influenced SLE disease activity and severity was correlated to dysbiotic changes of the oral microbiota present in periodontal diseases.